2000
DOI: 10.1001/archneur.57.4.600
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphorus Intoxication

Abstract: In every period of history, military leaders have wrestled between a desire to gain victory by using every possible means and a revulsion from resorting to poison. During the First World War, a European country cast aside the humanitarian tradition of its poets and philosophers and attacked its enemies with a wave of chlorine gas; the same nation, 30 years later, put to death 6 million human beings in gas chambers. But out of the industry of war gases, a few organophosphorus compounds, notably tabun and sarin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 6 publications
0
19
0
1
Order By: Relevance
“…Sadly however, given the prevailing scenario at the time, World War II, Schrader's work was mainly oriented toward the synthesis of chemical warfare agents. [2,3] However, after the war, the pharmacological properties of these agents were published leading to the realization of their potential use as insecticides and pesticides. This eventually led to the development of many more new OP compounds and their main use as insecticides and pesticides worldwide.…”
Section: Historical Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sadly however, given the prevailing scenario at the time, World War II, Schrader's work was mainly oriented toward the synthesis of chemical warfare agents. [2,3] However, after the war, the pharmacological properties of these agents were published leading to the realization of their potential use as insecticides and pesticides. This eventually led to the development of many more new OP compounds and their main use as insecticides and pesticides worldwide.…”
Section: Historical Aspectsmentioning
confidence: 99%
“…[23] Extrapolating these results to human beings, the WHO-recommended dose of pralidoxime is 30 mg/kg bolus followed by 8 mg/kg/ hour infusion. [19] The other limiting aspect of these studies were: (1) the randomization and masking techniques were not adequately described in both the studies [33,34] and (2) in the latter study the intervention arm included patients with more severe poisoning which could explain the increased frequency of intermediate syndrome, ventilator requirement, and mortality in the intervention arm. [36] Discrepancies between the robust rationale for the use of oximes and the failure to demonstrate their efÞ cacy in clinical trials can be understood if the limitations of oxime action are appreciated.…”
Section: Role Of Cholinesterase Reactivationmentioning
confidence: 99%
“…For this reason Khurana and Prabhakar 13 suggested that this syndrome, although known as organophosphate-induced delayed polyneuropathy, is inappropriately labeled because pyramidal involvement is usually present; initially, peripheral nerve involvement predominates, while corticospinal tract signs evolve more slowly. Our patient showed hyperreflexia of the upper limbs, with signs of pyramidal tract involvement.…”
Section: Type 2 Syndrome (Intermediate Syndrome)mentioning
confidence: 99%
“…Copious secretions may also occur in patients with bronchiectasis (usually purulent), endobronchial tuberculosis, and malignancies, especially in cases of bronchoalveolar carcinoma [1,2,3,4,5,6]. Intoxications of organophosphate, carbamate, and cyanide may also induce bronchorrhea [7,8,9]. …”
Section: Introductionmentioning
confidence: 99%